Investigation of the impact of comfort perception on the overall comfort of tight-fitting sportswear - Pengpeng Cheng; Daoling Chen (Journal of Engineered Fibers and Fabrics)
This paper focuses on tight-fitting sportswear as the research subject and investigates the dynamic influence of comfort perception on overall comfort. By developing a comprehensive evaluation system that encompasses both subjective and objective measures of comfort, this study systematically reveals the interactive mechanisms and dynamic characteristics of multi-dimensional comfort perceptions, including heat and humidity comfort, compression comfort, touch comfort, among others. The findings indicate that (1) local comfort levels fluctuate over time, with varying weights influencing overall comfort; (2) during 6 km/h exercise, key local discomfort sensations impacting overall comfort include restraint feelings of shank, stuffy feeling (cool feeling) of shank, restraint feeling of thigh, etc.; (3) there are significant correlations between stuffy feeling with sticky body feeling and humidity feeling respectively; additionally, notable correlations exist between sticky body feeling with humidity feeling and rough feeling. This study offers provides a more scientific basis for optimizing tight-fitting sportswear design.